Sensorless position control with a hydraulic stepper drive — Concept, compression modeling and experimental investigation. (May 2016) - Gradl, Christoph; Plöckinger, Andreas; Scheidl, Rudolf
Abstract: This paper presents a new type of a linear hydraulic stepper drive for sensorless positioning tasks in hydraulics. The drive transforms pulses sent to switching valves into quite precise motion steps. The drive is realized by a hydraulic cylinder piston unit which displaces defined fluid quantums by limited forward strokes of that piston. A test rig (hydraulic cylinder with a hydraulic stepper unit) was built and experiments were performed to study the positioning accuracy, repeatability, linearity and scattering range of the proposed stepper drive concept. Two different step sizes (5 µm and 15 µm) were tested and investigated. Also a computation model was developed for sensorless position estimation and verified by measurements. The results show the quite good accuracy of the model for all tested operating conditions. An application example is studied, the sensorless control of the deflection of an elastic beam. Its experimental testing was done by hardware in the loop simulation, where the computed beam force is imposed to the physical stepper drive via a controlled hydraulic force. The results proof the practical suitability of the drive concept.